2019
DOI: 10.1016/j.dib.2019.104492
|View full text |Cite
|
Sign up to set email alerts
|

Loading characteristics data applied on osseointegrated implant by transfemoral bone-anchored prostheses fitted with basic components during daily activities

Abstract: The data in this paper are related to the research articles entitled “Kinetics of transfemoral amputees with osseointegrated fixation performing common activities of daily living” (Lee et al., Clinical Biomechanics, 2007.22(6). p. 665–673) and “Magnitude and variability of loading on the osseointegrated implant of transfemoral amputees during walking” (Lee et al., Med Eng Phys, 2008.30(7). p. 825–833). This article contains the overall and individual loading characteristics applied on screw-type osseointegrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The variability of a dataset was determined using the percentage of variation (PV = absolute [[standard deviation/mean] x100]). Giving the inter and intra-variability of loading data reported previously, we considered that PV inferior or superior to 20% indicated a low and high variability, respectively (Frossard, 2013;Frossard, 2019;…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of a dataset was determined using the percentage of variation (PV = absolute [[standard deviation/mean] x100]). Giving the inter and intra-variability of loading data reported previously, we considered that PV inferior or superior to 20% indicated a low and high variability, respectively (Frossard, 2013;Frossard, 2019;…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this hypothesis could only be partially validated with the current understanding of loading profile applied by BAP estimated using inverse dynamics or measured with a transducer (Dumas et al, 2009;Dumas et al, 2017;Frossard et al, 2011b;Harandi et al, 2020;Niswander et al, 2020;Thesleff et al, 2018). Lee et al (2007Lee et al ( , 2008 reported some loading characteristics during walking, ascending and descending ramp and stairs for a cohort of TFAs fitted screw-type implants and basic components (e.g., mechanically passive knees, multi-axial foot-ankle) (Frossard, 2019;Lee et al, 2007;Lee et al, 2008b). Frossard et al (2013) presented a single-case study showing that the characterization of the loading profile using a series of extrema has the capacity to differentiate BAP fitted with a mechanical and MPK knees (Frossard, 2013).…”
Section: Current Knowledge Of Loading Profilementioning
confidence: 99%
See 1 more Smart Citation
“…However, it also means that any loads applied to the prosthesis are transferred directly to the bone-anchored implant and the periprosthetic bone which could be at risk of fracture. Several studies involving load cell measurements at the implant prosthesis interface have offered insights in the magnitude of the loading during ambulatory activities of daily living [22]- [24]. This data is valuable for numerical simulations such as finite element (FE) analyses to calculate periprosthetic and implant stress and strain.…”
Section: Introductionmentioning
confidence: 99%
“…Loading profiles have also been directly measured on cohorts of individuals fitted with transfemoral bone-anchored prostheses during a rehabilitation program (e.g., static load bearing, use of walking aids), standardized activities (e.g., walking in a straight line and around a circle, ascending and descending stairs and ramps), and unscripted daily activities (e.g., open environment, fall) [4,[15][16][17]19,26,27,35,[38][39][40][41][42][43][44][45][46]. These studies characterized the prosthetic loading profile using a range of variables associated with spatio-temporal characteristics (e.g., cadence, duration of gait cycle (GC) and support and swing phases), loading boundaries (e.g., maximum and minimum magnitude), a series of points of interest or local extremum (e.g., onset and magnitude of points of inflection between loading rate) and impulse [35,[38][39][40]43,46,[48][49][50]. Extraction of these variables for a large number of steps usually generated during ecological recordings was facilitated by the semi-automated detection of gait events (e.g., heel contact (HC), toe-off (TO)) and points of interest using set loading thresholds, as well as extraction of maximum or minimum loading magnitude within a time window selected manually, respectively [26,27,[51][52][53].…”
Section: Introductionmentioning
confidence: 99%